1983
DOI: 10.1152/ajpgi.1983.245.1.g99
|View full text |Cite
|
Sign up to set email alerts
|

Cell site and time course of DNA synthesis in pancreas after caerulein and secretin

Abstract: Pancreatic weight, [3H]-thymidine incorporation into DNA, labeling indices, and total DNA and RNA content were measured in rats treated with vehicle or 1 microgram/kg caerulein, 100 micrograms/kg secretin, or a combination of these peptides injected every 8 h for 1-5 days. Incorporation of [3H]thymidine into DNA increased 12-fold after 2 days of treatment with the combination of peptides. DNA content increased after 3 days and reached a level 1.8 times control after 5 days. Autoradiography showed that two cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…CCK given in an amount that will induce plasma levels that are comparable with those following a meal induced enzyme secretion as well as growth of the rat pancreatic gland (Solomon et al 1978) as indicated by significant increases in pancreatic weight, in total enzyme and protein contents as well as RNA and DNA (Solomon et al 1983). This trophic action of CCK can be obtained whether CCK was exogenously administered (Solomon et al 1983) or endogenously released either by feeding a high-protein diet (Morisset et al 1992) or following pancreatic juice diversion (Rivard et al 1991) and CCK exerts this trophic effect, not via a vagal afferent pathway, but directly on the pancreas, in vivo (Yamamoto et al 2003).…”
Section: Global Effects Of Gastrin and Cholecystokinin In The Gutmentioning
confidence: 99%
“…CCK given in an amount that will induce plasma levels that are comparable with those following a meal induced enzyme secretion as well as growth of the rat pancreatic gland (Solomon et al 1978) as indicated by significant increases in pancreatic weight, in total enzyme and protein contents as well as RNA and DNA (Solomon et al 1983). This trophic action of CCK can be obtained whether CCK was exogenously administered (Solomon et al 1983) or endogenously released either by feeding a high-protein diet (Morisset et al 1992) or following pancreatic juice diversion (Rivard et al 1991) and CCK exerts this trophic effect, not via a vagal afferent pathway, but directly on the pancreas, in vivo (Yamamoto et al 2003).…”
Section: Global Effects Of Gastrin and Cholecystokinin In The Gutmentioning
confidence: 99%
“…CCK stimulates normal growth of the pancreas (3)(4)(5)(6) and might be involved in growth of human pancreatic cancer (7,8). Exogenous administration of CCK can lead to pancreatic hyperplasia, dysplasia, and malignancies (9) and accelerates the growth of malignant pancreatic tissue (10 -12).…”
mentioning
confidence: 99%
“…CCK stimulates both exocrine secretion of diges tive enzyme from acinar cells and endocrine secretion of insulin from (3-cells (6) of the pancreas. Pancreatic cell growth (7,8) is also controlled by CCK. From a patho physiological point of view, it is suggested that endo genous CCK may be closely related to the etiology and development of pancreatitis, because CCK and its C-ter minal analogue caerulein have been reported to produce acute pancreatitis (9,10) or to worsen it (11) in experimen tal animals, and because pancreatitis patients frequently suffer from accompanying hypercholecystokininemia (12).…”
mentioning
confidence: 99%